Cost effectiveness of spread mitigation strategies for polyphagous shot hole borer Euwallacea fornicatus (Coleoptera: Curculionidae: Scolytinae) - Cook, David C.; Gardiner, Peter S.; Broughton, Sonya (Frontiers in Insect Science, 2023)
Polyphagous shot hole borer Euwallacea fornicatus Eichhoff was detected in Western Australia in September 2021, and an eradication campaign funded by the Commonwealth government is underway. As part of contingency planning, we examined the cost effectiveness of alternative control strategies that could be used to mitigate urban forest impacts and maintain the benefits of trees to the local communities if eradication was not feasible. At the time this work was undertaken, decision-makers were concerned about the potential need to replace all urban trees susceptible to attack. We considered this strategy alongside less destructive strategies and assessed their cost effectiveness in terms of material and labor costs and the loss of ecosystem services resulting from reduced tree foliage. Using a stochastic simulation model, we found that a strategy that involved pruning necrotic limbs and treating trees biennially with systemic insecticide was almost always more cost effective than removing infested trees and replanting to resistant varieties. We estimated this strategy would cost A$55-110 million over 50 years, while tree removal would cost $105-195 million. A third strategy using a mix of chemical suppression and tree removal was also considered in light of new information about the pest's host preferences. With an estimated cost of $60-110 million, this strategy was only slightly more expensive than using chemical suppression alone and could actually lead to eradication if the host range is as narrow as recent survey data suggests.